Traumatismes de L’Abdomen et du Périnée par Encornements de Bœufs au Centre Hospitalier Régional de Dapaong, Togo - Biréga Koutora; Abossisso Sakiye; Yves Aziz R. Nacanabo; Séna A. Tchalla; Efoé-Ga Amouzou; Mahèza Akpanahe; Tarek Alassani; Kokou K. Kanassoua; Badjona Songne-Gnamkoulamba (European Scientific Journal, ESJ, 2019)
Background: This paper focuses on describing the epidemilogical, lesional, and therapeutic aspects of abdomen and perineum bull horn trauma at Regional Hospital of Dapaong. Methodology: It is a descriptive retrospective study, which includes patientstreated for abdomen and perineum bullhorn trauma, in the surgery department of Regional Hospital of Dapaong from January 2016 to December 2018 (3 years). Results: 34 patients were treated for abdominal and perineal bullhorn injuries. They comprised of 31 men and 3 women, with an average age of 18.47 ± 16.14 years old (extremes: 6 and 70 years old). They were mainly less than 15 years old and were herd guards. The lesion report noted 9 cases of abdominal blunt trauma, 22 cases of abdominal wounds including 19 cases of penetrating wounds, and 3 cases of perineal wounds including 1 case of associated rectal lesion. Visceral lesions were varied and often associated. The care was mainly surgical. The short term evolution was marked by a local infection in 8 cases (23.5%). The prognosis was good in all cases. Conclusion: Bullhorn trauma is a frequent cause of abdomen and perineum injuries at Regional Hospital of Dapaong. The outcome after adequate care is often favourable. Objectifs: Décrire les aspects épidémiologiques, lésionnels et thérapeutiques destraumatismes de l’abdomen et du périnée par encornements de bœufs au Centre Hospitalier Régional de Dapaong. Méthodologie : Etude rétrospective descriptive incluant les dossiers des blessés de l’abdomen et du périnée par encornements de bœufs, pris en charge dans le service de chirurgie du CHR Dapaong, de Janvier 2016 à Décembre 2018 (3 ans). Résultats : Trente-quatre patients ont été pris en charge pour lésions traumatiques de l’abdomen et du périnée par coups de cornes de bœufs. Il s’agissait de 31 hommes et 3 femmes d’âge moyen de 18,47 ± 16,14 ans (extrêmes : 6 ans et 70 ans). La majorité des victimes avait moins de 15 ans, et était des gardes troupeaux. Le bilan lésionnel au niveau abdominal notait 9 cas de contusion et 22 cas de plaies dont 19 cas de plaies pénétrantes. Les lésions viscérales étaient variées et souvent associées. Au niveau périnéal, on notait 3 cas de plaies dont un cas de lésion rectale associée. La prise en charge était chirurgicale dans la majorité des cas. L’évolution à court terme était marquée par une infection locale dans 8 cas (23,5%). Le pronostic était bon dans tous les cas. Conclusion : Les encornements de bœufs constituent une cause fréquente de traumatismes de l’abdomen et du périnée au CHR Dapaong. L’évolution après prise en charge adéquate est souvent favorable.